Mối quan hệ giữa hình ảnh điểm đến, sự hài lòng và hành vi tương lai của du khách nội địa đối với điểm đến du lịch Đồng Tháp - Huỳnh Thị Thu, Sương; Huỳnh Quốc, Tuấn (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
The study aims to analyze the relationship between destination image, satisfaction, and future behavior of domestic tourists towards Dong Thap tourist destination. This research employs the quota sampling method with a sample size of 458. Data are collected through the direct interview method. Concomitantly, the method of analysis and verification of the linear structural model (SEM) is used. Research results show that cognitive image directly affects affective images and satisfaction, affective images directly impact visitor satisfaction, tourist satisfaction has a direct impact on revisit intention and electronic word of mouth. In addition, affective images have a direct influence on revisit intention while cognitive images have a direct impact on electronic word of mouth. In addition, the results also show that the affective images variable is a mediating variable between cognitive images and satisfaction, as well as revisit intention. Simultaneously, satisfaction was the mediating variable between cognitive images and revisit intention, similarity, and electronic word of mouth is the mediating variable between affective images, revisit intention, and electronic word of mouth.
Keywords: Destination image; Satisfaction; Electronic word- of- mouth; Revisit intention